El vínculo lenguaje-cultura en encuentros exolingüísticos dentro del servicio turístico - Boes Naderer, Joan Marie (2015)
This article discusses four aspects related to cultural and linguistic interaction within exolinguistic communication prevalent in tourism. The first aspect refers to the role of culture as an essential part of linguistic exchanges, and the second explains the unconscious nature of socialization and language processes. The third aspect is the pragmatics of communication in exolinguistic service interactions, and the fourth approaches the role of habitus in intercultural communication in tourism.